Caracterização ambiental das nascentes em área de preservação permanente, voltada à conservação da microbacia do córrego Quineira, em Chapada dos Guimarães – MT - Alves, Maria Aparecida da Silva (2015)
This work includes the resulting environmental problems of urban and uncontrolled expansion recorded in the city of Chapada dos Guimarães - MT. Data are presented concerning the environmental characterization of the springs in Permanent Preservation Area, aimed at conservation of the watershed stream Quineira. Its main objective is the environmental assessment of the watershed of this stream, and the state change its sources, with a view to proposing measures aimed at preserving their waterway, minimizing the effects of degradation. Water is the source of life, and the ideal springs are those that provide good quality, abundant and continuous water. To obtain the field data was developed environmental assessment in the watershed through Verah method, which allows a diagnosis of the whole area, and the characterization and identification of sources and its watercourse. Then carried the environmental characterization of the springs. The environmental characterization of the sources shows that they are partially preserved, making it necessary to adopt measures that allow the minimization of environmental damage and the recovery of altered and degraded area, intuited to protect water resources, the existing fauna and flora ensuring the quality of the stream in order to ensure better living conditions for the population.